EU fiscal governance and budget consolidation in Visegrád countries - Zh. N. Komissarova; E. A. Sergeev (Vestnik MGIMO-Universiteta)
Budget consolidations in Visegrád countries, which followed European financial and debt crisis, were mainly driven by external factors such as EU fiscal governance. Since the Visegrád countries have accomplished their consolidation effort, it seems topical to study their experience and assess the efficiency of consolidation measures. Involving descriptive statistical analysis, the authors posit that supranational impact on national budgets of Visegrád countries was quite efficient, as all economies concerned have accomplished a relatively sizeable fiscal consolidation. This happened largely due to the fact that the governments did not intend to lose vast amounts of funds from the EU budget. Such an option was quite feasible as a part of possible sanctions related to excessive deficit. The Czech Republic, Hungary, Poland and the Slovak Republic run different consolidations as to scale, structure and measures taken, though one could highlight some similarities. On the one hand, consolidations were to a great extent carried out through the means of indirect taxation, because they have a less distortive nature, given the structural characteristics of countries at issue. On the other hand, the governments refrained from raising direct taxes due to their distortive character. Hungary was the only country, which took some active measures in the field of corporate taxation, and subsequently suffered from drop in tax collection. The Visegrád countries did cut government expenditures, but strived to use the most effective instruments such as curbing employment in public sector. Further, there were some subsidiary factors at place that influenced consolidation pace. For example, three of four Visegrád countries are not members of a currency union, which inter alia contributed to monetizing government debt. At the same time, some measures taken by the countries, were of a quite formal nature. For instance, Hungary totally nationalized pension system in order to increase budget revenues. Nevertheless, all Visegrád countries reached deficit target without any revolutionary changes to main fiscal aggregates, which means that consolidations were at least nominally effective. However, cumulative deficit change was not fully accompanied by lowering debt and was by several times less than cumulative transfers from the EU budget. At the same time the budget consolidations in Visegrád countries could be called efficient as GDP growth rates restored, as did investors’ confidence and exports.